Benefits of gum arabic, for a solitary kidney under adverse conditions: A case study - Mehrab Dashtdar; Karima Kardi (Wolters Kluwer Health/LWW, 2018)
Gum Arabic (GA, called E-414 in the EU food industry), a natural biopolymer resin is a dried exudation obtained from the stems and branches of natural strains of Acacia Senegal (L) Willdenow. It consists mainly of high molecular weight polysaccharides and their calcium, potassium, and magnesium, which on hydrolysis yield arabinose, galactose, rhamnose, and glucuronic acid. Fermentable natural fiber of gum Arabic act as probiotics improves the absorption of minerals, especially calcium and helps to maintain a healthy balance of bacteria in the gastrointestinal (GI) tract. Extraction, transformation, or reprocessing of nitrogenous wastes (ammonia, urea, and uric acid) by the GI tract is a potentially low-cost means of switching for missing renal function. Binding of nitrogen compounds to be inert orally by administration of gum Arabic is the safe solution either in normal renal function or renal failures. In this study, clinically, we observed a case of solitary kidney under adverse condition long-term treating with gum Arabic the vast potential of bioactive phytochemicals as a nontoxic, efficient with uric acid and bilirubin lowering agent and anti-inflammatory effects, considering the gum Arabic as a potential therapeutic supplement, beneficial in chronic renal failure, cardiovascular disease, pain management, and dental health. Despite the nonexistent background concerning the benefits of gum Arabic, for a solitary kidney under adverse conditions, our study has confirmed that long-term consumption of gum Arabic not only has no side effect but also protects multi-organs damage from drug adverse reactions and consequences of baseline disease, including renal, vascular, dental and inflammatory diseases.